(untitled) (Research, Society and Development, 2022)
Currently, concerning to the renewable resources, the decrease in the consumption of raw materials and the research for sustainable operations have been emerging as an urgent demand in all segments of the market, emphatically including, the industry. Among the most diverse industrial segments, the pulp and paper industry is responsible for the consumption of large volumes of inputs, including water. Due to the high uptake of water from water courses and the high volume of effluent discharge, some alternatives have been investigated in order to reduce the impacts caused by this activity. Alternatives are reported for the improvement of water management and wastewater minimization aiming to an integrated way to shut down the water circuits of the production plants. For this closure step, resource management solutions are presented, such as partial water reuse, use of oxidative processes, treatments by using membranes, and enzymatic processes, which reveal techniques that can be sustainably applied to industrial processes, meeting the demands of society and fulfilling the Sustainable Development Goals, therefore preserving the environment and improving life’s quality of populations. In this context, this study aims to analyze, through a systematic review of previously established Brazilian databases, the alternatives and forms of reusing and recycling of water in industrial processes, focusing on closing circuits, with the characterization, benefits, and harms, of the actions performed by the pulp and paper industries.